Performance Competitive Advantage and Review on the Factors in the Company Cooperation - Achmad Daengs GS (Budapest International Research and Critics University, 2022)
The competitive advantage that can improve marketing performance can be grown by building learning relationship. This means that the company should be able to increase the activity of learning by facilitating the exchange of information, developing common learning area, and update their behavior in accordance with the terms of the stakeholders. These learning come from a variety of sources that are not even from stakeholders only, but also can obtain information derived from studies of scientists and academics. According to this case, the company can always obtain comprehensive understanding in determining any strategy that will be used. Relationship learning through the creation of common understanding are refer to the joint activities continually between the customer and the supplier that intended to create an understanding of information that could potentially affect the behavior. Everything is invaluable business supporting elements in smoothing activities. This includes various specific resources that can provide the supply of valuable information to the decision making process and strategic policy by the company.